LONG-TERM COCONUT LEAF PRUNING (CLP) EFFECTS ON CBFS: COCONUT-COFFEE AGROECOSYSTEM - L.H. Canja; S.S. Magat; R.Z. Margate (International Coconut Community, 2003)
A long-term study on the response of ‘Laguna’ tall (LAGT) palms and coffee intercrop to coconut leaf pruning (CLP) was conducted at the PCA-Davao Research Center from 1993 to 2001 to determine the effect of coconut leaf pruning on the productivity of coconut + coffee cropping system. The coconut leaf pruning technique did not significantly affect the yield and nutrition of coconut in all the years of observation. However, lower number of nut and weight of copra per tree were observed on palms with CLP than those without CLP, but with a slight improvement in copra weight per nut. Likewise, CLP did not affect the coffee yield and leaf nutrient levels. Among the coffee varieties tested, the Excelsa had the highest green bean yield. The Robusta (Ivory Coast and Philippine strains) and Arabica had similar yield and crop nutritional status. While they had similar leaf N, K and B contents that were higher than that of Excelsa, they also had lower leaf levels of Ca, Cl and S. Coffee needs, 1,000-3,000 foot-candles of sunlight, which is within the available light transmission (1,750-4,050 foot-candles) under palms with and without CLP. Hence, CLP is not necessary anymore in coconut with coffee intercrop.